Thelma the unicorn - Blabey, Aaron (2017)
Told in rhyme, Thelma the pony wants to be a unicorn--but when her wish comes true she discovers that there is a downside to fame, and realizes that she was happier at home with her friend.
"First published in Australia in 2015 by Scholastic Press, an imprint of Scholastic Australia"--Copyright page.
3-6
Keywords: Unicorns -- Juvenile fiction; Ponies -- Juvenile fiction; Self-acceptance -- Juvenile fiction; Wishes -- Juvenile fiction; Friendship -- Juvenile fiction; Stories in rhyme